KETERAMPILAN BERBICARA SEBAGAI KUNCI SUKSES DALAM PRESENTASI DAN NEGOSIASI BISNIS - Sri Mulyani Rusli; Nabilla Tri Juanda; Emil Davison; Belia Sabila; Witarni Wau; Ahmad Yuddi Apriliandi (STKIP Subang, 2026)
Effective speaking skills are a primary foundation for success in business presentations and negotiations, as they enable the delivery of persuasive ideas, build trust, and achieve optimal results. Empirical research from various journals shows that public speaking training significantly improves professional performance, with confidence increases of up to 70% among participants. This paper presents an in-depth literature-based analysis, including a synthesis methodology, quantitateve findings, and practical recommendations for the Indonesian business context.